Class Dismissed: A Critique of Weberian Perspective on Class and Ethnicity - Teal, Greg; Bai, David (Culture, 1981)
Given the relative paucity of Marxist analysis of ethnicity, non-Marxist social science has provided the dominant perspectives on the relations between class and ethnicity. An important concern of much of this research and writing has been to prove that ethnicity is predominant over class as the source both of social conflict and of social cohesion. In this paper current weberian perspectives on class and ethnicity, perspectives which, while paying some attention to social class, generally accord primacy to ethnicity in organizing social relations within and between ethnic groups, are critically examined. Evidence against such a view is presented, based on research conducted among Korean immigrants in Edmonton. Our research suggests that social class is a primary factor both in the formation and growth of the Korean community as well as in structuring social relations within the community.